2014
DOI: 10.1111/dme.12441
|View full text |Cite
|
Sign up to set email alerts
|

Substantial reductions in the number of diabetic ketoacidosis and severe hypoglycaemia episodes requiring emergency treatment lead to reduced costs after structured education in adults with Type 1 diabetes

Abstract: AimsTo determine the impact of structured education promoting flexible intensive insulin therapy on rates of diabetic ketoacidosis, and the costs associated with emergency treatment for severe hypoglycaemia and ketoacidosis in adults with Type 1 diabetes.MethodsUsing the Dose Adjustment For Normal Eating research database we compared the rates of ketoacidosis and severe hypoglycaemia during the 12 months preceding Dose Adjustment For Normal Eating training with the rates during the 12-month follow-up after thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 23 publications
10
93
1
2
Order By: Relevance
“…These data confirm earlier reports of a major reduction in severe hypoglycaemia 12 months after the ITTP and DAFNE 6, 10, 11, which is largely independent of HbA 1c (above or below 58 mmol/mol, 7.5%), insulin type or injection frequency. We propose the 76% reduced risk of severe hypoglycaemia arises from the total DAFNE education package, not just the basal insulin regimen.…”
Section: Discussionsupporting
confidence: 91%
“…These data confirm earlier reports of a major reduction in severe hypoglycaemia 12 months after the ITTP and DAFNE 6, 10, 11, which is largely independent of HbA 1c (above or below 58 mmol/mol, 7.5%), insulin type or injection frequency. We propose the 76% reduced risk of severe hypoglycaemia arises from the total DAFNE education package, not just the basal insulin regimen.…”
Section: Discussionsupporting
confidence: 91%
“…However, our findings demonstrate a clinically meaningful 70% reduction in DKA requiring hospitalisation, comparing favourably with recent UK DAFNE findings, demonstrating a 61% reduction in DKA [17].…”
Section: For Submission To Diabetes Research and Clinical Practicesupporting
confidence: 85%
“…The relative risk reduction of 52% following OzDAFNE training is consistent with international studies [1,8,17]. Thus, OzDAFNE offers an important clinical intervention in Australia, particularly given the absence of psycho-educational programs specifically targeting prevention of severe hypoglycaemia, e.g.…”
Section: For Submission To Diabetes Research and Clinical Practicesupporting
confidence: 80%
See 1 more Smart Citation
“…Studies have shown attendance at a DAFNE course reduces diabetes distress, severe hypoglycaemia and DKA admissions, along with small but significant changes in HbA1c (31,32). DAFNE is cost effective, evidenced by a 64% reduction in emergency health costs for DKA and severe hypoglycaemia (33). A service challenge is to make courses available to as many clinic attendees as possible.…”
Section: Accepted Articlementioning
confidence: 99%